Pengaruh Metode Joyfull Learning terhadap Hasil Belajar Ilmu Pengetahuan Sosial Peserta Didik Kelas V Sekolah Dasar - Alia Rohani; Nur Halizah; Rora Rizki Wandini; Seprina Ritonga (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
This study aims to determine the reality data whether there is a fun learning effect on learning outcomes in social studies subjects. This research was conducted in the second semester of the 2020/2021 academic year. The method used is an experimental method using a pre test and post test design. The Joyful Learning method is a fun interesting learning as a result of lessons that can direct attention to the learning being undertaken. This is made in such a way that it is in an atmosphere full of fun and not boring for students. The problem in this study is the result of student learning through Joyful Learning. Learning outcomes based on the results of the final test (post test) of students in the material for Preparation for Indonesian Independence, which can be obtained that the learning outcomes of students through Joyful Learning using the independence card media in social science subjects at State Elementary School 060873 in the city of Medan, Sumatra North.